A Review of the Impact of External Shocks on Monetary Policy Effectiveness in Non-WAEMU Countries - Sedegah, Kordzo; Odhiambo, Nicholas M. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
In this paper, the extant literature on the impact of external shocks on monetary policy effectiveness with reference to non-WAEMU countries is reviewed. The importance of this literature review is to provide contemporary perspectives to scholars and policymakers on the relevance of the incidence of external shocks to the effectiveness of monetary policy with reference to non-WAEMU countries. The literature reviewed in this study shows that, on the whole, the extent and the degree to which external shocks are transmitted to the domestic economy substantially depend on a plethora of features, namely the absence of exchange rate flexibility; a strong export concentration, especially with respect to commodities; the level of global economic integration; restricted capacities of production; the absence of competitiveness in exports; over-reliance on foreign aid; foreign reserves that are not adequate and capital account openness.